Great expectations [compact disc, unabridged] - Dickens, Charles. 1812-1870 (Tantor Media, 2008)
Charles Dickens' classic tale of orphan Philip Pirrip. Struggling to grow into a gentleman, Philip faces many truths about the world around him and ultimately himself as his expectations are tested and questioned.